Influencia de la comunicación digital emitida por el diario la hora en los ciudadanos del Sector La Loreto del cantón Quevedo año 2020 - Pachacama Aguilar, Miryan Lilibeth (2021)
Digital communication today is in full swing, as the world updates the type of communication as well. Therefore, worldwide this type of communication is used in all the activities that human beings carry out on a daily basis. The benefits that digital communication provides and presents, is significant, speed, immediacy, is essential in modern society, already dependent on digital. For this reason, even traditional media have opted for this type of communication, developing and implementing web pages, social networks, in which they currently also broadcast their information and content on different digital platforms. Which are most used to find information in them instantly through a click. That is why, in our research called, Influence of digital communication issued by the newspaper La Hora on the citizens of the Loreto sector of the Quevedo canton in 2020, we want to know the relationship of digital communication and the information issued by the Newspaper already mentioned. In relation to our study, we have developed it through the qualitative research instrument, called focus group, in which various opinions expressed by those present at the virtual meeting were collected, which was made up of 8 of the most loyal readers of the newspaper La Hora.